Non-accidental head injury: a consequence of deprivation?. Issue 12 (1st November 2009) - Mok, J Y Q; Jones, P A; Myerscough, E; Shah, A R F; Minns, R A
Abstract : Background: Non-accidental head injury (NAHI) is a significant personal and public health problem, with considerable mortality and morbidity. The evidence base for risk factors specific for NAHI is limited due to difficulties with case definition and study design. The risk factors associated with NAHI in infants was evaluated in this study, and the extent to which indices of deprivation influence this health problem was addressed. Methods: A 10-year prospective study was conducted in Scotland involving all paediatric hospitals and other general hospital departments admitting children. Subjects were children ≤2 years of age, with a diagnosis of "suspected NAHI". Socioeconomic characteristics of the index cases were compared to the general population, using the Scottish Index of Multiple Deprivation (SIMD) 2006. Results: There were highly significant differences (p<0.001) between the SIMD rank scores of the NAHI cases and scores for the whole Scottish population. For the cohort, SIMD ranks ranged from 34 to 6253 (median 1210; mean 1577) compared to the population range of 1–6505 (median and mean=3253). Similar differences were found for each of the component domains of income, employment, health, education, crime and housing (p<0.001). In contrast, the scores for "geographic access" (to essential service) were higher than for the whole population (p<0.001), indicating that the deprivation was not due to lack of local services. Conclusion: In Scotland, children who present with suspected NAHI originate predominantly from the most deprived areas of the community. Public health and intervention strategies should be focused in these areas.